HIKOYALARDA TARIXIY SHAXSLAR – TARIX BEZAGI - Amirqulova, Z.M. (SCIENCE and SOCIETY, 2020)
The article is devoted to the literary-artistic interpretation of the historical figures in the Uzbek literature of the independence period suchas Mahmud Ghaznavi, Firdausi, Beruni in the story "Repentance" by the famous writer Rahimjon Otayev.